Procyclicality in central counterparty margin models: A conceptual tool kit and the key parameters - Alper Odabasioglu (Bank of Canada, 2023)
Central counterparty (CCP) initial margin models are procyclical by nature, and CCPs use antiprocyclicality (APC) tools to mitigate this. However, despite the widespread use of such tools, margin models of CCPs around the world reacted severely to the heightened volatility during the March 2020 market turmoil. This triggered a debate globally on the adequacy of APC tools. We offer potential explanations for why those tools were not sufficient. We highlight that, to effectively mitigate procyclicality, the focus should be on the key parameters for both the margin model and the APC tools. One widely adopted APC tool established by the European Market Infrastructure Regulation is the stress period. We show that, to mitigate procyclicality with this tool, the main focus should not be on the calibration of its stressed margin level, but rather on the weight used to add this to the margin model. Further, the stress period tool can be highly effective, but only when its weight parameter is calibrated adequately high. These insights are essential for regulators to provide effective guidance on margin procyclicality, and for CCPs to appropriately design and calibrate their margin systems and procyclicality frameworks. To further serve these needs, we provide a novel conceptual tool kit for regulators and CCPs. The tool kit allows them to see a margin system's performance in procyclicality as well as in other competing objectives-such as margin coverage and cost of collateral-all in one place and for any combination of calibrations of the key procyclicality parameters. This feature lets regulators set outcomes-based procyclicality targets achievable by CCP margin models and APC tools. Moreover, it helps regulators design prescriptive procyclicality guidance in line with these desired outcomes-based targets. CCPs can use the tool kit to determine the set of parameter calibrations that satisfy the required procyclicality targets and perform sufficiently well in the other competing objectives
Keywords: G; G0; G01; G2; G23; G28; 330; Coronavirus disease (COVID-19); Credit risk management; Financial institutions; Financial markets; Financial stability; Financial system regulation and policies